Systemic and intestinal immunities after natural typhoid infection. - Sarasombath, S (1987)
A 2-year study of systemic and intestinal immunity to Salmonella typhi was performed in 14 patients who were suffering from typhoid fever in an attempt to extrapolate the mechanism of immune responses in this disease. The methods employed were the leukocyte migration inhibition agarose test for the measurement of systemic cell-mediated immunity. The systemic immunoglobulin G (IgG) and IgM that were specific to S. typhi and anti-O and anti-H agglutinins were measured by indirect enzyme-linked immunosorbent assay (ELISA) and the Widal test, respectively. The immunobead ELISA was used to measure total secretory IgA (SIgA), and indirect ELISA was used to measure SIgA that was specific to S. typhi in the intestinal lavage fluid. The results revealed that the patients developed various types of immune response to S. typhi that had various magnitudes and durations. After the onset of illness, the cell-mediated immunity persisted for 16 weeks; IgG, IgM, and anti-O and anti-H agglutinin persisted for 2 years, 16 weeks, 16 weeks, and 36 weeks, respectively. SIgA can persist in the gut for about 48 weeks. Thus, the immunities as a whole can barely persist beyond 1 year after the onset of illness, unless there are persistent booster stimulations by S. typhi bacilli that exist in the environment, and then the immunities may be lifelong.